Bird Community in Burung Island, Karimunjawa National Park, Central Java - MARGARETA RAHAYUNINGSIH; ANI MARDIASTUTI; LILIK BUDI PRASETYO; YENI A MULYANI (Society for Indonesian Biodiversity, 2007)
Burung Island is one of many islands in the Karimunjawa Islands that belong to Karimunjawa National Park conservation area. The purpose of this study is to discover the structure of bird community especially the species diversity and its habitat structure in Burung Island. The study was conducted on June 2006, November 2006, and June 2007 in Burung Island. The study was conducted by using point count method. The radius of each point is approximately 20 meters, while the time interval of observation on each count is 10 minutes. Thedistance between each point in this study is 100 m. The habitat observation was conducted by using habitat profile of tree cover vertical structure which was done descriptively by looking at the function of cover level to the present of bird or the relation between level and the present of bird in that location. The study’s result indicated that there are 15 recorded bird species from 10 family in the location, in whichfive species (five family) among them are protected by the government, which are Sterna sumatrana, Egretta sacra, Nectarinia jugularis, Caloenas nicobarica, and Falco moluccensis, and two of them were included in CITES (Convention on International trade in Endangered Species) appendices 1 and 2, which are Caloenas nicobarica and Falco moluccensis. The highest values of species diversity index (H’) and evenness index (E’) can be seen from the observation’s result of June 2007, which are 1.8837 and 0.836. The habitat of Burung Island is very suitable for Caloenas nicobarica, Egretta sacra, Sterna sumatrana, and Sterna bergii as a place for breeding. The use of vegetation level by bird in Burung Island is dominated by the use of low and base levels.© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Bird, community, Burung Island, Karimunjawa National Park